Hajj, Umrah and Ziyarah: In the Light of the Qurʼan and Sunnah - Abdul Aziz Abdullah Bin Baz (Lahore Darussalam, 2004)
This book outlines the necessary actions before, during & after performing Hajj, Umrah, and Ziyarah. It discusses topics ranging form the importance of Hajj to who should perform it. All proofs are given from the Qur'an & Sunnah.
Keywords: Muslim pilgrims and pilgrimages -- Saudi Arabia -- Mecca